Qualitative Analysis of Severe Incidents in Forensic Psychiatric Hospitals: Toward a Model of Forensic Vigilance - Clercx, Maartje (International journal of offender therapy and comparative criminology, 2025)
Forensic vigilance is a hypothesized specialty of forensic mental health professionals which seems to play a role in maintaining safety in forensic hospitals. It is unclear exactly how forensic vigilance relates to preventing incidents. We used standardized reports of severe incidents that occurred in forensic hospitals to investigate how forensic vigilance plays a role in the occurrence of incidents. Eight forensic psychiatric hospitals in the Netherlands contributed 69 anonymized incident reports, which were investigated by means of thematic analysis and interpretative phenomenological analysis. Analysis revealed five important themes. Four core skills needed by professionals, namely observation, integration, communication and action, which each need a number of prerequisites (e.g., knowledge). The fifth theme specifies that the professional needs to “connect the dots” meaningfully. This is a highly cyclical process in which the core four skills are steps. The process is unique to the forensic context in terms of how the “dots” are connected and weighed, and which risks need to be considered. We present a model of this process and prerequisites needed in professionals. This model can inform policy makers, aid assessment of and communication between forensic professionals and can form the basis of a training for forensic mental health professionals.